Changes in metabolic syndrome affect the health-related quality of life of community-dwelling adults - Yi-Hsuan Lin; Hsiao-Ting Chang; Yen-Han Tseng; Harn-Shen Chen; Shu-Chiung Chiang; Tzeng-Ji Chen; Shinn-Jang Hwang (Scientific Reports, 2021)
Abstract Metabolic syndrome (MetS) is associated with cardiovascular diseases, type 2 diabetes, chronic renal diseases, and all-cause mortality. Furthermore, MetS is associated with poor health-related quality of life (HRQOL). However, the impact of dynamic changes in MetS on changes in the HRQOL was not previously explored. This was an eight-year, prospective cohort study in which 906 middle-aged adults from Shipai, Taipei in northern Taiwan were enrolled during 2009–2010 (baseline). Of those sampled, 427 participants completed the follow-up investigation after 8 years. The HRQOL was measured using the Short Form Health Survey (SF-36). Other variables including age, sex, marital status, level of education, smoking, alcohol consumption, baseline body mass index, and changes in physical activity were adjusted. Compared with adults who never experienced MetS, adults with persistent MetS had a negative change in mental HRQOL (β − 4.20, 95% CI − 7.54 to − 0.86, p = 0.01). The negative changes of persistent MetS on the HRQOL were in the domains of vitality and mental health (β − 4.42, 95% CI − 8.10 to − 0.73 and β − 3.47, 95% CI − 6.90 to − 0.04, respectively). Women and overweight adults were vulnerable to the detrimental effects of persistent MetS. For better HRQOL, more resources should be devoted to reversing MetS in public health.